VISITORS’ WILLINGNESS TO PAY FOR VISITING THE PATENGA BEACH, BANGLADESH - Mohammad Mahfuzur Rahman (ASEAN Journal on Hospitality and Tourism, 2014)
Tourism has not yet been recognized as an industry in Bangladesh. There is a great dearth of studies to understand the significance of this sector to the nation. This study is a pioneer effort of its kind to evaluate the services of the Patenga Beach offered to its visitors. A total of 400 visitors were interviewed using a predesigned questionnaire. The study reveals that the maximum willingness to pay for entering into the beach without any reduction in the number of trips was BDT 475.69 inclusive of a beach entrance fee of BDT 100 (USD 1.25) per visitor. The study suggests that if the beach had well-planned facilities for the beach goers, they are willing to pay more for the development of the beach.